Some properties on semi-symmetric metric T-connection on Sasakian Manifold - Pandey, A.C.; Shukla, N. V.C. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In the present paper we have studied some properties of semi symmetric metric connection in almost contact metric manifold. In this paper we have studied some results related to quasi conformal curvature tensor, m-projective curvature tensor, con-harmonic curvature tensor, pseudo projective curvature tensor, T-connection and F-T connection.